ANTIBACTERIAL EFFECTIVENESS TEST OF RAMANIA LEAVES (Bouea macrophylla Griffith) FLAVONOIDS EXTRACT ON Aggregatibacter actinomycetemcomitans BACTERIA CAUSING AGGRESSIVE PERIODONTITIS - Noor Khalishah; Beta Widya Oktiani; Rosihan Adhani (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: Aggressive periodontitis is a disease that is mostly suffered by young patients with minimal local factors. The prevalence of this disease is approximately 8% in Indonesia, where Aggregatibacter actinomycetemcomitans bacteria are presented as dominant bacteria in this disease. Aggregatibacter actinomycetemcomitans is a gram-negative bacterium that is sensitive to flavonoids. Ramania leaves are natural substances which contain flavonoids. Flavonoids in ramania leaves can be applied as an antibacterial substance. Objectives: The objectives of this research are to determine and analyze the minimum inhibitory concentration and the minimum bactericidal concentration of flavonoids extract from ramania leaves at the concentration of 0.1%, 0.3%, and 0.5%, and analyze the antibacterial effectiveness on Aggregatibacter actinomycetemcomitans. Methods: True experimental design with pre and post-test with control group design was applied in this study. Antibacterial test using broth and agar dilution method was performed in a total of 5 treatment groups with 6 repetitions. Results:  All exract at 0.1%, 0.3% and 0.5% concentration demonstrated the ability to inhibit bacterial growth, and the minimum bactericidal concentration was found at 0.5% concentration. Result test for One way ANNOVA on minimum inhibitory concentration and Kruskal wallis test on minimum bactericidal concentration exhibited significant value of less than 0.05 presenting significant differences in some groups. Conclusion:  Minimum inhibitory concentration of ramania leaves flavonoid extract is effective on Aggregatibacter actinomycetemcomitans at the concentration of 0.1% and minimum bactericidal concentration of ramania leaves flavonoid extract is more effective at the concentration of 0.5%.Keywords: Aggregatibacter Actinomycetemcomitans, Aggressive Periodontitis, Dilution Method, Flavonoids, Ramania Leaves.